Kiai's Prophetic Leadership in the Development of Ra'iyatul Husnan Bondowoso Islamic Boarding School, East Java - Siti Hawiwik; Siti Aminah (Molang: Journal Islamic Education, 2026)
The leadership of kiai in Islamic boarding schools has a strategic role in determining the direction of institutional development in the midst of changing dynamics of the times. Leadership no longer only relies on charisma, but must also be value-based that is able to answer the challenges of modernity. Prophetic leadership is a relevant approach because it is based on prophetic values, namely siddiq (honest), amanah (responsibility), tabligh (communicative), and fathanah (intelligent). These values are the basis for building an adaptive, innovative, and sustainable pesantren management system. The focus of the research in this thesis is: 1) What is the leadership practice of siddiq kiai in the development of the Ra'iyatul Husnan Bondowoso Islamic Boarding School, East Java? 2) How is the leadership practice of  the nature of the kiai mandate in the development of the Ra'iyatul Husnan Bondowoso Islamic Boarding School, East Java? 3) How  is the leadership practice of the nature of tabligh kiai in the development of the Ra'iyatul Husnan Bondowoso Islamic Boarding School, East Java? 4) What is the leadership practice of the nature of fathanah kiai in the development of the Ra'iyatul Husnan Bondowoso Islamic Boarding School in East Java? This research is a qualitative research with a type of case study research. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses the qualitative data analysis of the Milles and Huberman model, namely: data condensation, data presentation, and conclusion drawing and verification. The validity of the data is carried out through source triangulation and technique triangulation. This study came to the conclusion that: 1) The nature of siddiq is reflected in information openness, honesty, transparency, and the suitability between words and actions that make kiai an example for all pesantren residents. 2) The nature  of trust is realized through the management of pesantren that is transparent, accountable, responsive to the needs of students, as well as the development of facilities and infrastructure in a sustainable manner to support the welfare and well-being of the Islamic boarding school. The learning process of the students. 3) The nature of tabligh can be seen from the communication skills of the kiai that are effective, open, and easy to understand, as well as the existence of space for all elements of the pesantren to convey aspirations, criticisms, and suggestions in the policy-making process. 4) The nature  of fathanah is reflected in the ability of the kiai to think strategically, innovatively, and wisely through the development of the education system, the use of technology, the improvement of pesantren facilities, and the decision-making that Prioritizing the needs of students and the progress of Islamic boarding schools.